Role of carnitine acetylation in skeletal muscle - Yasuro Furuichi; Naoko Goto-Inoue; Nobuharu L. Fujii (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Carnitine is known for its role in the transport of long-chain fatty acids into the mitochondrial matrix for subsequent β-oxidation. In addition, carnitine acts as an acceptor of excess acetyl-CoA and forms acetylcarnitine to relieve inhibition of pyruvate dehydrogenase. Recent studies have demonstrated that carnitine acetylation is essential for glucose homeostasis, and its dysfunction induces metabolic failure. Furthermore, it has been suggested that acetylcarnitine might be exported from skeletal muscle into the blood. Considering that acetylcarnitine is a bioactive molecule involved in glucose metabolism and neuroprotection, we expect that acetylcarnitine production is beneficial to the body. In this article, we reviewed recent knowledge on the role of carnitine acetylation in glucose metabolism within skeletal muscle. Furthermore, this article introduces acetylcarnitine as a physiologically active substance and discusses carnitine dynamics during exercise.